Influence of phosphorus fertiliser use on two New Zealand pasture insect pest communities - Katrin G. Hewitt; Rainer W. Hofmann; Olivier J. Ball; Chanatda Somchit; Colin M. Ferguson; Ray Moss; Racheal H. Bryant; Alison J. Popay (Agriculture, Ecosystems & Environment, 2025)

Effects of nitrogen reduction on the agronomic characteristics, quality, and water and fertilizer use efficiency of tomato (lycopersicon esculintum mill.) between drip fertigation and negative-pressure fertigation - Jiajia Wang; Changjun Wang; Huaiyu Long; Ray Bryant; Patrick J. Drohan; Fengchen Qu; Dichuan Liu; Guolong Zhu; Zhuan Wang; Le Wang (Irrigation Science, 2025)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

The mean seasonal cycle in relative sea level from satellite altimetry and gravimetry - Richard D. Ray; Bryant D. Loomis; Victor Zlotnicki (Journal of Geodesy, 2021)
Satellite altimetry and gravimetry are used to determine the mean seasonal cycle in relative sea level, a quantity relevant to coastal flooding and related applications. The main harmonics (annual, semiannual, terannual) are estimated from 25 years of gridded altimetry, while several conventional altimeter “corrections” (gravitational tide, pole tide, and inverted barometer) are restored. To transform from absolute to relative sea levels, a model of vertical land motion is developed from a high-resolution seasonal mass inversion estimated from satellite gravimetry. An adjustment for annual geocenter motion accounts for use of a center-of-mass reference frame in satellite orbit determination. A set of 544 test tide gauges, from which seasonal harmonics have been estimated from hourly measurements, is used to assess how accurately each adjustment to the altimeter data helps converge the results to true relative sea levels. At these gauges, the median annual and semiannual amplitudes are 7.1 cm and 2.2 cm, respectively. The root-mean-square differences with altimetry are 3.24 and 1.17 cm, respectively, which are reduced to 1.93 and 0.86 cm after restoration of corrections and adjustment for land motion. Example outliers highlight some limitations of present-day coastal altimetry owing to inadequate spatial resolution: upwelling and currents off Oregon and wave setup at Minamitori Island.

A review of regulations and guidelines related to winter manure application - Jian Liu; Peter J. A. Kleinman; Helena Aronsson; Don Flaten; Richard W. McDowell; Marianne Bechmann; Douglas B. Beegle; Timothy P. Robinson; Ray B. Bryant; Hongbin Liu; Andrew N. Sharpley; Tamie L. Veith (Ambio, 2018)

Application of manure to no-till soils: phosphorus losses by sub-surface and surface pathways - Peter J. A. Kleinman; Andrew N. Sharpley; Lou S. Saporito; Anthony R. Buda; Ray B. Bryant (Nutrient Cycling in Agroecosystems, 2009)